INTERCESSION IN THE QUR'AN CRITICAL ANALYSIS INTERPRETATION OF AL-MARAGHI - Kazuba, Mahfudz; M., M. Ghalib; Abubakar, Achmad; Firdaus (Program Pascasarjana, UIN Alauddin Makassar, 2022)
Man will not be separated from intercession because in human life, even until death, he still needs intercession. People who genuinely have faith in Allah swt. Submit and obey the sharia to Him. Islam sets the standard of morality based on the provisions of Allah and His Messenger. Therefore, what is seen as good by Allah and His Messenger, must be good. Moreover, vice versa, it cannot be Allah swt. He was judging falsehood as good behavior because the falsehood of its essence must be immoral. Thus in every explanation relating to intercession,